Default Spread dan Term Spread sebagai Variabel Proxy Siklus Bisnis pada Model Fama-French - Edwin Hendra; Kim Sung Suk (Binus Business Review, 2015)
This research aims to apply the Fama-French models and test the effect of alternative variable of bond yield spread, default spread (RBBB – RAAA and RAAA – RF), and the term spread (RSUN10-RSUN1), as proxy variables of the business cycle, in IDX stock data during 2005-2010. Four types of asset pricing models tested are Sharpe-Lintner CAPM, Fama-French models, Hwang et al.model, and hybrid model. The results showed that the size effect and value effect has an impact on excess stock returns. Slopes of market beta, SMB, and HML are more sensitive to stock big size and high B / M. Default spreads and term spreads in Hwang et al. model can explain the value effect, and weakly explain the size effect, meanwhile the power of explanation disappeared on Hybrid models. Based on the assessment adjusted R2 and the frequency of rejection of non-zero alpha, is found that the hybrid model is the most suitable model.